KECERDASAN VISUAL-SPASIALeL DALAM MENYELESAIKAN SOAL PISA SISWA KELAS X SMA NEGERI 1 JEMBER DITINJAU DARI GENDER - Alfarisi, Muhammad Alfan; Sunardi, Sunardi; Kurniati, Dian (Kadikma, 2015)
Abstract. This research is a descriptive research with qualitative approach. The purpose of this research was to discribe visual-spatial intellegence of X MIPA 6 grade and X MIPA 7 grade based on students gender. Subject of this research consist of 67 students. Data collection methods in this research are Test and interviews. Indicators in this research were arranged based on four characteristics of visual and spatial intellegence, namely imagining, conceptualizing, problem-solving and pattern-seeking. The results of test and interviews will be analyzed by looking at achievements of the indicators from each characteristic of visual-spatial intellegence. Based on data analysis obtained tendency both male students and female students were only able to fulfill the first and second indicator from 4 indicators of imagining characteristics ; for conceptualizing characteristics, both male and female students tend to be able to fulfill each indicator; for problem-solving characteristic both male students and female students tend to be only able to fulfill the first indicator but the others were not; Next for pattern-seeking characteristic both male students and female students were able to search for the patterns and capable to fulfill any given indicators. Keywords : Visual-spatial intellegences, characteristics of visual-spatial intellegence